2016
DOI: 10.1053/j.jrn.2015.09.002
|View full text |Cite|
|
Sign up to set email alerts
|

Validating Appetite Assessment Tools Among Patients Receiving Hemodialysis

Abstract: Objective To test the performance of appetite assessment tools among patients receiving hemodialysis. Design Cross-sectional. Setting Seven dialysis facilities in Northern California. Subjects 221 patients receiving hemodialysis. Intervention We assessed five appetite assessment tools [self-assessment of appetite, subjective assessment of appetite, visual analogue scale (VAS), Functional Assessment of Anorexia/Cachexia Therapy (FAACT) score and the Anorexia Questionnaire (AQ)]. Main outcome measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…Indeed, in a recent review about the performance of appetite assessment tools among patients receiving hemodialysis, it has been shown that the prevalence of poor appetite varies considerably from 6% to 24%. 13 In the present study, besides LTI and BCMI, phase angle, a direct measure of bioimpedance, was also lower among patients with poor appetite. The phase angle has been validated as a prognostic indicator in critically ill patients 28,29 and in patients on dialysis, the lower phase angle was associated with worse nutritional parameters and mortality.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, in a recent review about the performance of appetite assessment tools among patients receiving hemodialysis, it has been shown that the prevalence of poor appetite varies considerably from 6% to 24%. 13 In the present study, besides LTI and BCMI, phase angle, a direct measure of bioimpedance, was also lower among patients with poor appetite. The phase angle has been validated as a prognostic indicator in critically ill patients 28,29 and in patients on dialysis, the lower phase angle was associated with worse nutritional parameters and mortality.…”
Section: Discussionsupporting
confidence: 53%
“…A variety of tools have been developed and used to evaluate appetite in patients with CKD. Some studies used the question about food intake from the subjective global assessment (SGA), 8,15 while other investigators assessed the discomfort caused by the lack of appetite in a given period of time, 11,13 and most of them used part or the entire content of the ADAT. 6,9,10,[16][17][18] ADAT is an extensive questionnaire (44 questions) about appetite developed in the United States and validated for the population on hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30 min before recording hypothalamic activity, the presence/absence of anorexia was investigated using the Functional Assessment of Anorexia/Cachexia Therapy (FAACT) questionnaire, which has been recently endorsed by the European Society for Clinical Nutrition and Metabolism (ESPEN) as a reliable tool to assess disease‐associated anorexia . As recently shown, a FAACT score ≤ 30 is indicative of the presence of anorexia …”
Section: Methodsmentioning
confidence: 99%
“…The time frame of reference for the three appetite tools was represented by the moment they were completed (current appetite). We additionally administered the self‐assessment of appetite changes, which investigates present appetite vs. appetite over the last month (increased, decreased, or unchanged) …”
Section: Methodsmentioning
confidence: 99%
“…We additionally utilized leptin/BMI and adiponectin/BMI ratios in our analyses accounting for the well-known associations between leptin and adiponectin with adiposity, as previously shown (22,23).…”
Section: Biomarkersmentioning
confidence: 99%